Peran Pemerintah Desa dalam Pengembangan Objek Wisata Pasir Bentang di Desa Sukamnah Kecamatan Sindangkasih Kabupaten Ciamis - Muhamad Sopyan; Irfan Nursetiawan; Regi Refian Garis (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
This research is motivated by the role of the Village Government in developing the Pasir Span Tourism Object in Sukamanah Village, Sindangkasih District, which is not yet optimal. The aim of this research is to determine the role of the village government in developing the Pasir Bentang tourist attraction in Sukamanah Village. The method used in this research is descriptive analysis. There were 7 informants. Data collection techniques are literature study, field study (observation and interviews) and documentation. The author uses qualitative data analysis techniques by processing data from interviews and observations to draw conclusions so that they can answer the problems in the research. Based on the research results, it is known that: The village government has not optimally carried out its role in developing the Pasir Bentang tourist attraction considering that there are several indicators of the dimensions of the role that have not been optimal, causing the development of the Pasir Bentang tourist attraction to be less than expected. This includes, among other things, a lack of response from the community in activities. deliberations on planning the development of tourist attractions and the lack of an active role in managing tourist attractions. Budget limitations mean that it has not been optimal in structuring the Pasir Bentang tourist attraction. Apart from that, the collaboration between Pokdarwis and LMDH has not been able to increase the development of the tourist attraction due to the lack of clear authority in managing the tourist attraction. As well as the lack of encouraging community participation in realizing sustainability and cleanliness at the Pasir Bentang tourist attraction and not being supported by the availability of human resources who have an understanding of the concept of tourism management so that tourism promotion activities have not been carried out routinely.